Study on Total Protein and Amino Acid Profile of Milkfish (Chanos chanos) Meat and Its Product from Sidoarjo, East Java - Tambunan, Jeny Ernawati; Suprayitno, Eddy; Sulistiyati, Titik Dwi; Panjaitan, Mikchaell Alfanov Pardamean (Research Journal of Life Science, 2022)
Milkfish is one of the most cultivated fish species in Indonesia because these fish have a high tolerance to the various environmental conditions of tropical waters and are resistant to many pests and diseases. This preliminary research was conducted to analyze the amino acid composition contained in milkfish meat and its product. A total of 20 fresh milkfish were obtained from ponds in Sidoarjo, East Java, in September 2020. Amino acid composition and protein content were analyzed. Based on its protein content, milkfish has been classified as a source of high protein. The amino acid profile of milkfish consists of approximately 17 types of amino acids. Glutamic acid, the amino acid present in the highest concentration, makes milkfish very popular.